The Causative “To Be or Not to Be” in the Light of the Predicate-Argument Model - Petkova, Ekaterina (Slavic Languages Today: Categories, Structures and Processes, 2021)
This article discuses sentences expressing the causal relation and the combinatorics of meanings within them. The analysis draws on Małgorzata Korytkowska’s theory of types of predicate-argument positions, which is applied to two types of non-object argument positions: cause and effect. The study focuses on complex phenomena, such as consecutio temporum and the truth conditions of sentences, which serve for the semantic differentiation of semantic-syntactic positions. The aspectual analysis of sentences expressing the causal relation calls into question the ontological status of the correlation itself.